Cross-Layer Design and Performance Analysis of Quality of Service Control Scheme for Wireless Body Area Networks - Kento Takabayashi; Hirokazu Tanaka; Chika Sugimoto; Katsumi Sakakibara; Ryuji Kohno (IEEE Access, 2017)
We analyze and optimize the performance of a quality of service (QoS) control scheme in a cross-layer design for wireless body area networks (WBANs). Smart health monitoring systems that incorporate WBANs and multimedia services have recently been studied and developed. In a WBAN system, wearable and implantable vital sensor nodes can include various types of sensors. Thus, QoS control is a key technique to ensure that different kinds of data are communicated in such a system. In previous work, we proposed an optimal QoS control scheme that employs a multiplexing layer for priority scheduling and a decomposable error control coding scheme for WBANs. However, a cross-layer approach, which is an important technique to optimize the QoS requirements of various kinds of data, has not been considered. In this paper, we utilize a cross-layer design between physical and medium access control layers and analyze and compare the performance of our QoS control scheme and a standard scheme. Numerical results demonstrate that the proposed scheme outperforms the standard scheme. The proposed system achieves a more than 5 dB gain compared with the standard scheme relative to the probability of unsuccessful transmission. We also show that a scheduled access protocol outperforms a random access protocol, except for delay time. In addition, we optimize some factors of the proposed system and the standard scheme in a cross-layer design.